Solid electrolyte, its manufacturing method, and lithium secondary battery including the same
The development of an oxygen-doped argyrodite solid electrolyte with specific compositional ranges addresses the handling challenges of sulfide-based electrolytes, ensuring stability and improved performance in all-solid-state batteries.
Patent Information
- Application Number
- JP2024537916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-22
- Filing Date
- 2022-12-21
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-12-21
Smart Images

Figure 2025501581000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a battery, and more particularly to a solid electrolyte, a method for producing the same, and a lithium secondary battery including the same. [Background technology]
[0002] Recently, interest in high-capacity batteries has increased due to the rapid increase in demand for small power-driven devices such as IT mobile devices, electric bicycles, and small electric cars. Due to the increased demand for high-capacity batteries, active research has been conducted on the safety and energy density of the high-capacity batteries.
[0003] As a result, research into all-solid-state batteries is being actively conducted as a material to improve the safety and increase the energy density of existing secondary batteries. All-solid-state batteries are batteries that replace the liquid electrolyte used in existing lithium secondary batteries with a solid electrolyte, and can improve the safety of batteries by eliminating the use of flammable solvents and eliminating the risk of fire or explosion caused by reactions such as the decomposition reaction of conventional electrolytes. In addition, lithium metal or lithium alloys can be used as the negative electrode material, which can improve the energy density relative to the mass and volume of the battery.
[0004] The solid electrolyte used in the all-solid-state battery is generally an inorganic solid electrolyte, and various researches have been conducted on sulfide-based solid electrolytes having the same composition as Li6PS5Cl, which has an argyrodite structure in the all-solid-state battery. However, the sulfide-based solid electrolyte has a problem that it is difficult to handle in general air due to a side reaction with moisture. Summary of the Invention [Problem to be solved by the invention]
[0005] The technical problem to be solved by the present invention is to provide an all-solid-state battery that is easy to handle in the atmosphere.
[0006] Another technical problem to be solved by the present invention is to provide a method for manufacturing an all-solid-state battery having the above advantages.
[0007] Another technical problem to be solved by the present invention is to provide a lithium secondary battery, including an all-solid-state battery, having the above-mentioned advantages. [Means for solving the problem]
[0008] The solid electrolyte according to an embodiment of the present invention may be an argyrodite type in which a part of the halogen element is doped with oxygen. (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y (1≦x≦2, 0.01≦y≦0.3). In one embodiment, the solid electrolyte may satisfy the following formula 1: <Expression 1> 3.5≦[S] / [P]≦4.1 (In the above formula 1, [S] and [P] respectively represent the atomic percentages of S and P.)
[0009] In one embodiment, the solid electrolyte may have XRD peak values at 2θ=15.5°±0.5°, 2θ=18°±0.5°, 2θ=25.5°±0.5°, 2θ=30.2°±0.5°, and 2θ=32.5°±0.5°deg. In one embodiment, the ionic conductivity of the solid electrolyte before exposure to the atmosphere may be 3.1 mS / cm or more. In one embodiment, the solid electrolyte may have a reduction rate of 35% or less in ionic conductivity after exposure to the atmosphere compared to before exposure to the atmosphere.
[0010] A method for manufacturing a solid electrolyte according to another embodiment of the present invention includes the steps of preparing a lithium source material, a sulfur source material, a halogen source material, and a doping source material, mixing the source materials, and heat-treating a resultant obtained by mixing, and the doping source material may be a source material containing oxygen. In one embodiment, the doping source material may include a phosphate-based compound.
[0011] In one embodiment, the phosphate-based compound may include at least one selected from the group consisting of Li3PO4, Li4SiO4, Li4GeO4, Li3BO3, and Li3AlO3. In one embodiment, in the step of preparing the raw material, the phosphate-based compound may be added in an amount of 0.01 to 0.3 mol % based on 100 mol % of the solid electrolyte.
[0012] In one embodiment, the lithium source material may be Li2S, the sulfur source material may be P2S5, and the halogen source material may be LiCl. In one embodiment, the doping source material may include a phosphate-based compound.
[0013] In one embodiment, Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y (1≦x≦2, 0.01≦y≦0.3). In one embodiment, the solid electrolyte may satisfy the following formula 1: <Expression 1> 3.5≦[S] / [P]≦4.1 (In the above formula 1, [S] and [P] respectively represent the atomic percentages of S and P.)
[0014] A lithium secondary battery according to another embodiment of the present invention includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and a solid electrolyte disposed between the positive electrode and the negative electrode, and the solid electrolyte may be an argyrodite type in which a portion of a halogen element is doped with oxygen. In one embodiment, the solid electrolyte is Li (xy-x-5y+7) P (1-y) S(xy-x-5y+6) Cl x-xy O 4y It may have a composition of (1≦x≦2, 0.01≦y≦0.3).
[0015] In one embodiment, the solid electrolyte may satisfy the following formula 1: <Expression 1> 3.5≦[S] / [P]≦4.1 (In the above formula 1, [S] and [P] respectively represent the atomic percentages of S and P.) Effect of the Invention
[0016] The all-solid-state battery according to one embodiment of the present invention is Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y By including the composition (1≦x≦2, 0.01≦y≦0.3), it is possible to provide an all-solid-state battery that is stable in the air, has excellent initial capacity, and has a long life compared to existing sulfide-based solid electrolytes.
[0017] The method for manufacturing an all-solid-state battery according to another embodiment of the present invention can manufacture an all-solid-state battery having the above-mentioned advantages.
[0018] A lithium secondary battery according to another embodiment of the present invention may provide a lithium secondary battery including an all-solid-state battery having the above-mentioned advantages. [Brief description of the drawings]
[0019] [Figure 1] 1 is a graph versus XRD peak intensity according to various embodiments of the present invention. [Diagram 2] 1 is a flowchart for a method for manufacturing a solid electrolyte according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, a first part, component, region, layer or section described below can be referred to as a second part, component, region, layer or section without departing from the scope of the present invention.
[0021] The terminology used herein is merely for the purpose of referring to specific embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the text clearly indicates otherwise. As used herein, the meaning of "comprises" is intended to embody certain properties, regions, integers, steps, operations, elements and / or components, and does not exclude the presence or addition of other properties, regions, integers, steps, operations, elements and / or components.
[0022] When an element is described as being "on" or "above" another element, it may be exactly on or above the other element, or it may have other elements between them. In contrast, when an element is referred to as being "directly on" another element, there are no other elements between them.
[0023] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted as having a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted in an ideal or very formal sense unless defined.
[0024] Moreover, unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight.
[0025] FIG. 1 is a graph of XRD peak intensity according to various embodiments of the present invention.
[0026] 1, the solid electrolyte according to an embodiment of the present invention may be an argyrodite type in which a portion of a halogen element is doped with oxygen. The solid electrolyte is not a solid electrolyte interphase (SEI) film that occurs at the interface of an electrode material as in the initial charge / discharge reaction after the manufacture of a battery, but a solid material having lithium (Li) ion conductivity that can be used as a substitute for an electrolyte and a separator when designing a battery, for example.
[0027] The solid electrolyte of the present invention having the above composition is a compound containing sulfur, and may be a sulfide-based solid electrolyte. Specifically, the argyrodite type may have an argyrodite type structure containing lithium (Li), phosphorus (P), sulfur (S), and halogen elements such as chlorine (Cl). The solid electrolyte may be in the form of particles or powder, and may be crystalline or amorphous.
[0028] In one embodiment, the solid electrolyte is Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y (1≦x≦2, 0.01≦y≦0.3). The solid electrolyte has a halogen element doped with oxygen, so that the ionic conductivity and cell performance of the solid electrolyte are not deteriorated, the moisture stability is improved, and the stability can be maintained even when exposed to the atmosphere.
[0029] In one embodiment, the solid electrolyte of the present invention satisfies the following formula 1: <Expression 1> 3.5≦[S] / [P]≦4.1 (In the above formula 1, [S] and [P] respectively represent the atomic percentages of S and P.)
[0030] The at % ratio of the sulfur to the phosphorus may be 3.5 to 4.1. When the value of the formula 1 satisfies the above range, there is an advantage in that deterioration of the ion conductivity of the solid electrolyte and the cell performance can be prevented.
[0031] If the value of formula 1 exceeds the upper limit, the conductivity may decrease, whereas if the value of formula 1 exceeds the lower limit, the stability against moisture may decrease.
[0032] In one embodiment, the solid electrolyte may have a peak intensity at a predetermined position in an X-ray diffraction pattern measured by an X-ray diffractometer (XRD). Specifically, the solid electrolyte having the composition may have XRD peak values of 2θ=15.5°±0.5°deg, 2θ=18°±0.5°deg, 2θ=25.5°±0.5°deg, 2θ=30.2°±0.5°deg, and 2θ=32.5°±0.5°deg in the X-ray diffraction pattern.
[0033] In one embodiment, the solid electrolyte may be characterized in that the XRD peak values do not fall within the ranges of 2θ=17°±0.5°deg and 2θ=21.5°±3°deg. The XRD peak values of 2θ=17°±0.5°deg and 2θ=21.5°±3°deg correspond to impurity peaks, and by having the solid electrolyte in which such peaks are not observed, atmospheric stability and electrochemical stability can be improved.
[0034] FIG. 2 is a flow chart for a method for manufacturing a solid electrolyte according to one embodiment of the present invention.
[0035] Referring to FIG. 2, a method for manufacturing an argyrodite-type solid electrolyte according to another embodiment of the present invention includes a step of preparing a lithium source material, a sulfur source material, a halogen source material, and a doping source material (S100), a step of mixing the source materials (S200), and a step of heat-treating the resultant mixture (S300).
[0036] In one embodiment, the step (S100) of preparing a lithium source material, a sulfur source material, a halogen source material, and a doping source material may, for example, prepare Li2S as the lithium source material, P2S5 as the sulfur source material, and LiCl as the halogen source material.
[0037] In one embodiment, the doping source material may be a source material containing oxygen. For example, the doping source material may be a phosphate-based compound. By using the phosphate-based compound as a doping source material, the solid electrolyte is more stable in the atmosphere than the existing argyrodite solid electrolyte, and the initial capacity and lifespan are improved.
[0038] In one embodiment, the phosphate-based compound may include at least one selected from the group consisting of Li3PO4, Li4SiO4, Li4GeO4, Li3BO3, and Li3AlO3. Specifically, the doping source material may be Li3PO4.
[0039] In one embodiment, the step of preparing the raw material (S100) may include adding the phosphate-based compound in an amount of 0.01 to 0.3 mol %. When the amount of the phosphate-based compound added corresponds to the range, a sulfide-based solid electrolyte containing a certain ratio of oxygen (O) element can be included, and a solid electrolyte with excellent moisture stability can be provided.
[0040] If the amount of the phosphate-based compound added exceeds the upper limit, there are problems such as the formation of an impurity phase and a decrease in ionic conductivity, whereas if the amount of the phosphate-based compound added exceeds the lower limit, there are problems such as the difficulty in confirming the air stabilization effect.
[0041] In one embodiment, the argyrodite-type solid electrolyte is Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y It may have a composition of (1≦x≦2, 0.01≦y≦0.3).
[0042] In the method for producing a solid electrolyte, the step of preparing Li2S, P2S5, LiCl, and Li3PO4 raw materials (S100) is to prepare Li2S, P2S5, LiCl, and Li3PO4 raw materials having the above-mentioned composition of the solid electrolyte. (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y The raw material can be controlled to correspond to (1≦x≦2, 0.01≦y≦0.3).
[0043] The step of mixing the raw materials (S200) may be performed through mechanical mixing or chemical mixing. For example, the mechanical mixing may utilize a paint shaker, a ball mill, a bead mill, a homogenizer, a hammer mill, an oil mill, or the like, and the chemical mixing may utilize a melt quenching method, or the like. Specifically, the step of mixing the raw materials (S200) may be performed by mixing the raw materials using an oil mill.
[0044] The step of heat-treating and synthesizing the resultant obtained by mixing (S300) is a firing process, which is a step of applying heat to the resultant obtained by mixing. In one embodiment, the step of heat-treating and synthesizing the resultant obtained by mixing (S300) can be performed after performing additional processes such as drying, stirring, washing, granulation, and classification, as necessary.
[0045] In one embodiment, the heat treatment can be performed in an inert atmosphere, which can be, by way of non-limiting example, an H2, He, or Ar atmosphere. Specifically, the inert atmosphere can be an Ar atmosphere.
[0046] In one embodiment, the heat treatment can be performed at a temperature of 300° C. or more. Specifically, the heat treatment can be performed at a temperature range of 300 to 800° C., specifically, 350 to 700° C., more specifically, 400 to 600° C. If the heat treatment is performed at a temperature lower than the above range, there is a problem that the solid-phase reaction and the crystallization reaction do not proceed smoothly.
[0047] Thus, the solid electrolyte produced through the above steps is Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y (1≦x≦2, 0.01≦y≦0.3) and the solid electrolyte has excellent air stability and improved initial capacity and life. The detailed description of the solid electrolyte as a result of the synthesis is the same as that of FIG. 1 to the extent not inconsistent.
[0048] A lithium secondary battery according to another embodiment of the present invention may include a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and a solid electrolyte disposed between the positive electrode and the negative electrode. The solid electrolyte may refer to FIG. 1 described above, and may be the same as FIG. 1 described above to the extent that it is not inconsistent with the solid electrolyte.
[0049] The positive electrode is LiCoO2, LiNiO2, LiNi x Mn y O2, Li 1+z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z The positive electrode may be any one of the group consisting of LiFePO4, LiCoO2, NCM811, and NCM622, and the combinations thereof, and the x may be 0.3 to 0.8, the y may be 0.1 to 0.45, and the z may be independently 0 to 0.2. More specifically, the positive electrode may be LiFePO4, LiCoO2, NCM811, and NCM622.
[0050] The negative electrode may be made of a carbonaceous material such as natural graphite, artificial graphite (mesophase carbon microbeads), pyrolytic carbon, mesophase pitch based carbon fiber, mesophase pitches, petroleum or coal tar pitch derived cokes, or the like; a lithium-containing titanium composite oxide (LTO), a metal (Me) of Si, Sn, Li, Zn, Mg, Cd, Ce, Ni, or Fe; an alloy composed of the above metals; or an oxide of the above metals (MeO x ); and the metals (Me) and carbon composites, and combinations thereof. Specifically, the negative electrode may be made of natural graphite particles, synthetic graphite particles, Sn particles, Li4Ti5O 12 The negative electrode may be made of natural graphite, artificial graphite, silicon, or a combination thereof.
[0051] Thus, a lithium secondary battery containing the solid electrolyte of the present invention as a component can maintain stability in the air and can improve the initial capacity and life. EXAMPLES
[0052] Hereinafter, specific examples of the present invention will be described. However, the following examples are specific examples of the present invention, and the present invention is not limited to the following examples.
[0053] [Comparative Example 1] (Preparation of Li6PS5Cl) A common argyrodite solid electrolyte, Li6PS5Cl, was prepared.
[0054] [Comparative Example 2] (Li 5.5 P.S. 4.5 Cl 1.5 (Production) Li 5.5 P.S. 4.5 Cl 1.5is synthesized through dry milling. The dry milling is carried out by mixing Li2S, P2S5, and LiCl at 300 rpm for 8 hours using a planetary mill, forming pellets at 300 MPa, and synthesizing them through heat treatment at 550℃ in an argon (Ar) atmosphere.
[0055] [Example 1] (Li 5.465 P 0.99 S 4.465 Cl 1.485 O 0.04 (Production) Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y The solid electrolyte was used with x=1.5 and y=0.01, and Li2S, P2S5, LiCl, and Li2PO4 were quantified. 0.01 mol% of Li3PO4 was added, and the mixture was mixed at 300 rpm for about 8 hours using an oil mill. The mixture was then pelletized at 300 MPa and heat-treated at 550℃ in an argon (Ar) atmosphere.
[0056] [Example 2] (Li 5.395 P 0.97 S 4.395 Cl 1.455 O 0.12 (Production) Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y The same procedure as in Example 1 was carried out, except that the solid electrolyte was changed to y=0.03 and 0.03 mol % of Li3PO4 was added.
[0057] [Example 3] (Li 5.325 P 0.95 S 4.325 Cl 1.425 O 0.20 (Production) Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4yThe same procedure as in Example 1 was carried out, except that the solid electrolyte was changed to y=0.05 and 0.05 mol % of Li3PO4 was added.
[0058] [Example 4] (Li 5.15 P 0.90 S 4.15 Cl 1.35 O 0.40 (Production) Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y The same procedure as in Example 1 was carried out, except that the solid electrolyte was changed to y=0.10 and 0.1 mol % of Li3PO4 was added.
[0059] [Example 5] (Li 4.80 P 0.80 S 3.80 Cl 1.20 O 0.80 (Production) Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y The same procedure as in Example 1 was carried out, except that the solid electrolyte was changed to y=0.20 and 0.2 mol % of Li3PO4 was added.
[0060] [Example 6] (Li 4.45 P 0.70 S 3.45 Cl 1.05 O 1.2 (Production) Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) Cl x-xy O 4y The same procedure as in Example 1 was carried out, except that the solid electrolyte was changed to y=0.30 and 0.3 mol % of Li3PO4 was added.
[0061] Table 1 below shows the electrochemical evaluation and moisture stability evaluation for Comparative Examples 1 and 2 and Examples 1 to 6. The electrochemical evaluation was an evaluation of ion conductivity at 30°C 0.1C, and the electrochemical evaluation of the solid electrolyte for Comparative Examples 1 and 2 and Examples 1 to 6 was performed using a powder cell, and after the electrolyte was injected, it was densified at 300 MPa. Then, the cell was fastened at a pressure of 70 MPa using SUS electrodes, and 10 mV was applied at 25°C to measure the impedance. The impedance means that the ion conductivity is measured.
[0062] The moisture stability was evaluated by leaving 2 g of a powdered solid electrolyte in a dry room with a dew point of about -40°C for about 12 hours, and then recovering the electrolyte to measure impedance, for example, ionic conductivity.
[0063] The at% ratio of sulfur to phosphorus can be confirmed through the results of EDS component mapping. Specifically, the reduction rate means ((ionic conductivity after air exposure-ionic conductivity before air exposure) / (ionic conductivity before air exposure))×100[%].
[0064] [Table 1]
[0065] From Table 1, it can be seen that the ionic conductivity of the solid electrolyte of the present invention before exposure to the atmosphere is in the range of 3.1 to 9.0 mS / cm, and from Examples 1 to 6, it can be seen that the ionic conductivity increases as the amount of Li3PO4 added increases. Specifically, in the case of the ionic conductivity before exposure to the atmosphere, it can be seen that the ionic conductivity decreases as the amount of Li3PO4 added increases, and through the ionic conductivity and reduction rate after exposure to the atmosphere, it can be seen that the reduction rate of the ionic conductivity decreases as the amount of Li3PO4 added increases. Since the reduction rate of the ionic conductivity decreases, it can be seen that the stability to the atmosphere is excellent as the amount of Li3PO4 added increases. The electric conductivity may have a fluctuation range depending on the particle size, and the electric conductivity may change during the pulverization process, so the examples of the present invention do not limit the present invention. Specifically, the solid electrolyte may have an ionic conductivity reduction rate of 35% or less after exposure to the atmosphere compared to before exposure to the atmosphere. The solid electrolyte satisfies a reduction rate of 35% or less in ionic conductivity when comparing before and after exposure to the atmosphere, thereby solving the problem of being difficult to handle in general air due to side reactions with moisture, and providing a solid electrolyte with improved moisture stability without deterioration of ionic conductivity and cell performance.
[0066] The present invention is not limited to the above examples and / or embodiments, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention pertains can understand that the present invention can be embodied in other specific forms without changing the technical idea or essential characteristics of the present invention. Therefore, the above embodiments and / or examples should be understood to be illustrative in all respects and not restrictive.
Claims
1. An argyrodite-type solid electrolyte in which some of the halogen elements are doped with oxygen.
2. Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) C x-xy O 4y 2. The solid electrolyte according to claim 1, having a composition of (1≦x≦2, 0.01≦y≦0.3).
3. The solid electrolyte according to claim 1 , which satisfies the following formula 1: <Formula 1> 3.5≦[S] / [P]≦4.1 (In the above formula 1, [S] and [P] mean the atomic percentages of S and P, respectively.)
4. 2. The solid electrolyte according to claim 1, having XRD peak values of diffraction peaks at 2θ = 15.5° ± 0.5°, 2θ = 18° ± 0.5°, 2θ = 25.5° ± 0.5°, 2θ = 30.2° ± 0.5°, and 2θ = 32.5° ± 0.5° deg.
5. providing a lithium source material, a sulfur source material, a halogen source material, and a doping source material; mixing the raw materials; and heat treating the result obtained by mixing; The doping source material is a source material containing oxygen.
6. The method for producing an argyrodite-type solid electrolyte according to claim 5 , wherein the doping source material includes a phosphate-based compound.
7. The phosphate-based compound is Li 3 P.O. 4 , Li 4 SiO 4 , Li 4 GeO 4 , Li 3 B.O. 3 , and Li 3 AlO 3 The method for producing an argyrodite-type solid electrolyte according to claim 6, comprising at least one selected from the group consisting of:
8. 8. The method for producing an argyrodite-type solid electrolyte according to claim 7, wherein in the step of preparing the raw material, the phosphate-based compound is added in an amount of 0.01 to 0.3 mol % based on 100 mol % of the solid electrolyte.
9. The lithium source material is Li 2 S, The sulfur source material is P 2 S 5 and 6. The method for producing an argyrodite-type solid electrolyte according to claim 5, wherein the halogen source material is LiCl.
10. Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) C x-xy O 4y 6. The method for producing an argyrodite-type solid electrolyte according to claim 5, wherein (1≦x≦2, 0.01≦y≦0.3).
11. The method for producing an argyrodite-type solid electrolyte according to claim 5 , wherein the solid electrolyte satisfies the following formula 1: <Formula 1> 3.5≦[S] / [P]≦4.1 (In the above formula 1, [S] and [P] mean the atomic percentages of S and P, respectively.)
12. a positive electrode comprising a positive electrode active material; a negative electrode comprising a negative electrode active material; and a solid electrolyte located between the positive and negative electrodes; The solid electrolyte of the lithium secondary battery is an argyrodite type in which a part of halogen elements is doped with oxygen.
13. The solid electrolyte is Li (xy-x-5y+7) P (1-y) S (xy-x-5y+6) C x-xy O 4y 13. The lithium secondary battery according to claim 12, having a composition of (1≦x≦2, 0.01≦y≦0.3).
14. The lithium secondary battery according to claim 12, wherein the solid electrolyte satisfies the following formula 1: <Formula 1> 3.5≦[S] / [P]≦4.1 (In the above formula 1, [S] and [P] mean the atomic percentages of S and P, respectively.)
Citation Information
Patent Citations
Sulfide solid electrolyte based on oxygen doping and preparation method of sulfide solid electrolyt
CN108493479A
Lithium oxide argyrodites
WO2020061354A1
Solid electrolyte, electrode mixture and battery
WO2021251347A1
Cited By
Modified lithium sulfide, sulfide solid electrolyte, method for preparing the same, and battery
JP2026164614A